The Visualization of the Batik Cloth Stamping Machine Using Augmented Reality at the Yogyakarta City Crafts and Batik Center - Sena, Prasdika Widas; Setiafindari, Widya; Dwiyanto, Fikri (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2025)
The batik stamp machine is one of the machines used by the Center for Crafts and Batik to make batik cloth. This machine has been automated using PLC (Programmable Logic Controler) which makes machine can be controlled by computer. The batik products produced are 15 page/month. From the results of the production carried out, it has not met the production target which is targeted to reach 50 page/month, so there is a need for innovation in the machine which will increase production. The redesign of this stamp machine using technology Augmented Reality namely visualizing a 3D image to be object 3D so that it can evaluate the object to be made before it reaches the development machine stage so as to reduce costs. The process that must be carried out is to make a drawing of a batik stamp machine including: machine size, and machine specifications, make a license on Vuvoria Engine to making markers on software unity. The method used in the development of Augmented Reality is single marker method i.e. one image marker can only display single objects, so the method cannot display multi object. From the results of making Technology Augmented Reality is a redesign carried out on the stamping machine for batik at the Center for Crafts and Batik is a rare step that can be done to increase the productivity of making batik so that it meets the production targets expected by the Center for Crafts and Batik. So it is necessary to visualize the machine with AR technology so that it becomes an evaluation material for batik cloth stamping machines and reduces the cost of the development of machines which in the future will be able to increase batik production.